Educational Management for Student Support Systems in the Digital Era - khantayaphon, tidsadee; Khantayaphon, Jakree; Tidtor, Peerapat; Boonsong, Kanchana; Phetchsom, Nipa (Journal of MCU Phetchaburi Review, 2025)
Abstract This academic article aims to study approaches to managing student care and support in the digital age, which is a crucial issue in developing educational quality that aligns with the changing societal context. This study reviews concepts, theories, and research related to student care and support, educational management systems, and digital technologies applied in teaching and learning management. The findings reveal that effective management of student care and support in the digital age requires integration between traditional student care systems and digital technology. School administrators must have a vision for technology implementation, teachers need to develop digital competencies, and there must be clear monitoring and evaluation systems. Such implementation will result in more comprehensive, rapid, and efficient student care and support. Keywords: Educational management, Student care and support, Digital technology, Education in digital age, Student support system